The role of corporate social responsibility and corporate sustainability in alleviating the European refugee crisis - Samothraki, Anna L. (Human rights review, 2025)
The refugee crisis has been one of the most challenging problems in Europe in recent years, causing sudden and significant political turmoil in most of its member states. Notwithstanding the international treaties on refugee protection, a crucial issue is the reluctance of many local communities to offer refugees access to the labour market and daily social activities. In addition to the difficulties regarding social acceptance, there are also many other legal, social, ethical and political obstacles for refugees. This discussion is mainly limited to the realm of politics and ethics with very few references to the field of management, Corporate Social Responsibility (CSR) and corporate sustainability (CS) where the issues of marginalized people, minorities and vulnerable people are frequently addressed. To fill this gap, this article aims to discuss the role of CSR and CS in overcoming obstacles for refugees in their effort to integrate into the labor market. Through a narrative literature review and snowballing techniques, a theoretical framework has been developed to outline the ways that CSR and CS can assist refugees in overcoming different types of obstacles in host countries. Finally, in the discussion, ways in which CSR and CS literature could play a critical role in this discussion are highlighted and how the private sector could relieve the refugee crisis through CSR strategies.